Risk factors associated with increased prevalence of abdominal aortic aneurysm in women. Issue 9 (22nd June 2016) - Chabok, M.; Nicolaides, A.; Aslam, M.; Farahmandfar, M.; Humphries, K.; Kermani, N. Z.; Coltart, J.; Standfield, N.
Abstract: Background: Four randomized trials of men aged 65–80 years showed that aneurysm‐related mortality was reduced by 40 per cent by ultrasound screening. Screening is considered economically viable when the prevalence of abdominal aortic aneurysm (AAA) is 1·0 per cent or higher. This is not the case for women, in whom the prevalence of AAA is less than 1 per cent. The aim of the present investigation was to determine the prevalence of AAA 3·0 cm or larger in women screened with ultrasound imaging, the risk factors associated with AAA in this population, and whether high‐risk groups can be identified with an AAA prevalence of 1 per cent or greater. Methods: Demographic data and risk factors were collected from the first 50 000 women who attended for private cardiovascular screening in the UK. Tests included ultrasound screening for AAA, ankle : brachial pressure index (ABPI), carotid duplex imaging for carotid atherosclerosis, and electrocardiography for atrial fibrillation. Results: AAA was detected in 82 of 50 000 women screened; these aneurysms were rare below the age of 66 years (7 of 24 499). In the 66–85‐years age group there were 72 AAAs in 25 170 women (0·29 per cent). Univariable analysis demonstrated that a history of stroke/transient ischaemic attack (TIA), hypertension, smoking, atrial fibrillation, ABPI of less than 0·9 and internal carotid artery stenosis of at least 50 per cent were associated with an increased prevalence of AAA ( P < 0·001). In multivariable linear logistic regression of risk factors, age 76 years or more, history of stroke/TIA, hypertension and smoking were independent predictors of AAA. This model had an area under the receiver operating characteristic (ROC) curve (AUC) of 0·711 (95 per cent c.i. 0·649 to 0·772) and could identify 2235 women who had 22 AAAs (prevalence 0·98 per cent). By adding ABPI, atrial fibrillation and carotid stenosis, the prediction improved to an AUC of 0·775 (0·724 to 0·826). This model could identify 3701 women who had 58 AAAs (prevalence 1·57 per cent). Conclusion: This report should stimulate consideration of a targeted AAA screening programme for women aged over 65 years. Abstract : Worth considering